Juca, An Embedded Mobile Robotics Board for Education - Pinto, Matheus Leitzke; Starke, Renan Augusto; Vitor, Adriano (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
Mobile robotics has become an essential tool in educational environments due to its dynamic and practical nature, which allows students to experiment with real-world applications. This paper introduces “Juca”, an embedded mobile robotics board designed specifically for education. Juca combines affordability, expandability, and robust functionality, making it suitable for classroom and competition environments. Key features include modular hardware akin to Arduino shields, support for differential drive robots, and seamless integration with educational programming platforms. Experimental results demonstrate its effectiveness in fostering hands-on learning and engagement.